The Effect of Rebranding, Perceived Quality and Brand Awareness on Brand Loyalty at Truntum Padang Hotel Customers - Fikhri Ahmad Arbi; Siti Aminah (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the impact of the influence of Rebranding, Perceived Quality and Brand Awareness on Brand Loyalty on Truntum Padang Hotel customers. The population in this research is Truntum Padang Hotel Visitors. The sample in this study used the theory put forward by Ghozali and found a sample of 102 respondents. The primary data collection method in this study uses a questionnaire in the form of a GForm. The data analysis technique in this study uses PLS (Partial Least Square). The results of this study indicate that the Rebranding variable has a positive and significant influence on Brand Loyalty, the Perceived Quality variable makes a positive and significant contribution to Brand Loyalty, and the Brand Awareness variable influences Brand Loyalty positively and significantly. The results of this study also show that brand awareness makes a positive and significant contribution to brand loyalty. With a high level of brand awareness, customers will be more aware of matters relating to the Truntum Padang Hotel brand.